2010
DOI: 10.1097/jtn.0b013e3181ff2789
|View full text |Cite
|
Sign up to set email alerts
|

Parental Recognition of Postconcussive Symptoms in Children

Abstract: Evaluation of current emergency department discharge instructions and parental recognition of symptomatology requiring further care for traumatic brain injury (TBI) is not well understood. A convenience sample of 105 parents of children aged 5 to 17 years who were seen and discharged from the pediatric emergency department with TBI was identified. Parents were surveyed by telephone 2 to 5 days after injury and a questionnaire was completed regarding identification of TBI symptoms. This study demonstrated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 6 publications
0
39
0
Order By: Relevance
“…When parents were asked about individual symptoms, approximately 47% of parents who initially reported an asymptomatic child identified 1 or more symptoms in their child. 38 Similarly, Hajek et al 39 found that while parents and children reported similar postconcussion symptoms, on average children reported more symptoms than their parents. When parents were asked to identify signs and symptoms of concussion, most could identify concussion symptoms, but 44% missed emotional outbursts and 28% missed difficulty sleeping.…”
Section: Resultsmentioning
confidence: 97%
“…When parents were asked about individual symptoms, approximately 47% of parents who initially reported an asymptomatic child identified 1 or more symptoms in their child. 38 Similarly, Hajek et al 39 found that while parents and children reported similar postconcussion symptoms, on average children reported more symptoms than their parents. When parents were asked to identify signs and symptoms of concussion, most could identify concussion symptoms, but 44% missed emotional outbursts and 28% missed difficulty sleeping.…”
Section: Resultsmentioning
confidence: 97%
“…Studies have revealed that concussion symptoms may be underidentified by parents 10,11 and underreported by children. 12 Various surveys of youth sports' coaches have revealed that many have misconceptions about concussion, which can be improved with education.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study of parent ability to recognize concussion symptoms after receiving verbal and written instructions in the emergency department showed that most parents were unable to identify concussion symptoms in their children. 29 This suggests that more robust discharge education is necessary. Prior work has shown that making an appointment for parents at the time of discharge increases family attendance at follow-up visits.…”
Section: Discussionmentioning
confidence: 99%